Effects of an Empowerment Program on Self-care Agency for Elders with Hypertension - Boonchun, Natsurang; Ucharattana, Prangtip; Punsakd, Wattana; Meehardsai, Nittaya (Nursing Science Journal of Thailand, 2011)
Purposes: The objectives of this action research study were todevelop an empowerment program to increase self-care agencyin elders with uncontrollable hypertension and to examine theeffects of the program. Design: Action research. Methods: A total of 78 elders with uncontrollable hypertensionwere recruited using convenience sampling. Exclusion criteriawere paralysis, critical heart disease, renal failure, and anycondition inhibiting self care. A practice guideline based onGibson’ s process of empowerment was developed for use in theprogram which consisted of self respect, problem analysis,reflection, goal setting, supportive planning, evaluation and selfcarebehavior. The subjects joined the empowerment groups 3times. Data analysis using descriptive statistics and t-test wereperformed for quantitative data, and content analysis forqualitative data. Main findings: Elders’ self-care behaviors between pre and postprogram enrollment were significantly different (p < .05). Bloodpressure was significantly decreased after program enrollment(p < .05). Content analysis was revealed that elders were notaware of high blood pressure, lacked of knowledge, anddepended on physicians’ orders. After the program, the subjects’self-care behaviors were positively changed with, for example,increased awareness of diet control and daily exercise, increasedparticipation in elder’s group activities for reducing stress, andconsistently self-monitoring in medication use. Conclusion and recommendations: The use of anempowerment program to develop self-care agency can increaseself care behaviors and reduce blood pressure in elders. Theprogram should be applied in primary health care settings toempower the elders for controlling their blood pressureeffectively.